Integrating Technology in Tahfidzul Qur'an School Development Programs - Nugroho, Apriyanto; Astutik, Anita Puji (Indonesian Journal of Islamic Studies, 2024)
Islamic educational institutions face the challenge of integrating information technology into their programs to enhance their long-term sustainability and effectiveness. However, there is limited research on how tahfidzul Qur'an programs can incorporate technological advances for improved school development. This study addresses this gap by exploring the development of an information technology-based tahfidzul Qur'an school program at Al Azhar International Islamic Boarding School. Utilizing an exploratory descriptive qualitative method, the research gathers insights from the school's founder to identify key strategies. The results indicate that careful planning, monitoring, and evaluation are essential for achieving long-term educational goals. Human resource development, seen as a valuable institutional asset, must be prioritized through regular training. Additionally, optimizing information media is crucial to increase the institution's visibility and attract prospective students. The novelty of this study lies in its focus on integrating technology into religious education management. The implications suggest that effective use of technology in tahfidzul Qur'an school programs can align graduate outcomes with the institution's vision and mission, setting a model for similar educational programs seeking sustainable development. Highlights: Strategic long-term planning is vital for program success. Human resource quality is crucial for institutional growth. Technology optimization attracts potential students and ensures program sustainability. Keywords: School Development, Information Technology, Tahfidzul Qur'an, Educational Planning, Human Resource Training